The effect of perceived organizational support and employee care on turnover intention and work engagement: a mediated moderation model using age in the post pandemic period - Li, Qin; Mohamed, Rosmah; Mahomed, Anuar; Khan, Hanna (Mary Ann Liebert, 2022)
The purpose of this study was to adopt the well-established and mature job demands–resources model (JD-R), and to extend its model to work engagement and turnover intention of frontline healthcare personnel. Using the cross-sectional survey and partial least squares path modeling tools, the results showed that perceived organizational support had a negative impact on the turnover intention of frontline healthcare staff. This finding is important because it shows how the medical system managers can buffer the negative impact of a lack of job resources on the work engagement of employees in terms of personal strategies, such as the psychological pressure in coping with a high workload. Compared with employee care, perceived organizational support for the respondents had a positive impact on work engagement, whereas work engagement had a negative impact on turnover intention. This study successfully integrated the literature on job resources, work engagement, and turnover intention to determine the real needs of frontline medical personnel.